Checklist of scaleworms (Polychaeta: Polynoidae) - Hanley, J. R. (In: Morton B, editor. Proceedings of the fourth international marine biological workshop: The marine flora and fauna of Hong Kong and southern China. The marine flora and fauna of Hong Kong and southern China III. Hong Kong University Press, Hong Kong, 1992)
hirteen species of polynoid scaleworm are recorded from material collected during 11-29 April 1989. Nine of the species are recorded from Hong Kong for the first time. The checklist is incomplete as a number of new species (15) and records (25) are still the subject of taxonomic research.